STEM in ecological issues (STEMCology): Block-based programming for computational thinking in pre-service elementary teachers - Hikmatunisa, Nenden Permas; Nurussama, Alfiana; Rahayu, Teten Ginanjar; Nuraeni, Fitri; Wulan, Neneng Sri; Yogiarni, Tiara; Ravy, Hun (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2026)
Pre-service elementary teachers face persistent challenges in developing computational thinking (CT) alongside ecological literacy, an area underexplored at the elementary teacher-education level and lacking a validated, population-specific instrument. This study designed and evaluated STEMCology, a design-based research (DBR) framework integrating STEM principles, biological ecological content, and Tynker block programming, to develop pre-service elementary teachers' CT competencies. A one-group pretest-posttest design was used with 74 participants from two classes at one university. The framework comprised four phases: analysis and exploration, identifying eight ecological anchor topics and contextualizing a 29-item, five-dimension CT scale; design and construction, where students built flowchart-guided, ecology-themed Tynker games; evaluation and reflection, in which MSI-converted CT scores showed statistically significant improvements across all five dimensions (p < 0.05), with creativity showing the largest gain (N-Gain = 0.401, medium category) and the remaining dimensions showing low-category gains (0.089 – 0.199); and redesign and refinement, where students revised their games based on evaluation findings to enhance ecological accuracy, logical structure, and playability. These findings suggest that ecologically grounded, block programming-based interventions can be meaningfully integrated into teacher education curricula to cultivate CT competencies in future elementary school teachers.